Fake News Monitoring with Machine Learning and Natural Language Processing: Leveraging Machine Learning and Natural Language Processing for Fake News Detection (Journal of Advances and Scholarly Researches in Allied Education, 2018)
News is a pivotal aspect of our life. In everyday life, current news is helpful to upgrade in-formation that occurs far and wide. So the majority of people groups lean toward watching news the more significant part of the people groups by and enormous favor perusing paper promptly toward the beginning of the day getting a charge out of with a cup of tea. If the news is fake, that will delude people groups, some of the time, and fake words are used to get out bits of gossip about things or influence some political pioneer positions due to fake news. So it is significant to locate the fake news. So we proposed a framework to recognize fake news, yet now daily's information on the web or social media is expanding immeasurably, and it is so chaotic to identify whether the news is fake. Here we proposed fake news identification tools dependent on grouping, for example, Logistic relapse (LR), Naïve Bayes (NB), Support vector machine (SVM), etc. We look at all Machine Learning strategies for recognizing fake news.